Regulation of Eclipta prostrata L. components on cigarette smoking‐induced autophagy of bronchial epithelial cells via keap1‐Nrf2 pathway. Issue 8 (4th May 2018) - Ding, Shumin; Hou, Xuefeng; Wang, Fujing; Wang, Gang; Tan, Xiaobin; Liu, Ying; Zhou, Yuanli; Qiu, Huihui; Sun, E.; Jiang, Nan; Li, Zihao; Song, Jie; et al.
Abstract: Cigarette smoking extract (CSE)‐induced autophagic injury has been regarded as an important contributor to the pathogenesis of lung cancer. We previously found that Eclipta prostrata L. component (CCE) reduced CSE‐induced bronchial epithelial cells damage. However, the mechanism remains unknown. Human normal bronchial epithelial cells (NHBE) were exposed to CSE to establish stress model. Nrf2‐siRNA and Keap1‐siRNA transfection were performed. mRFP‐GFP‐LC3 dual fluorescence and transmission electron microscopy were used to observe the autophagic characteristics. CCE prevented CSE‐induced Nrf2 transfer into cytoplasm and up‐regulated Keap1 level of NHBE cells. Furthermore, CCE significantly increased p‐p16, p‐p21 and p‐p53 phosphorylation levels in Nrf2‐siRNA‐ or Keap1‐siRNA‐transfected cells. As demonstrated by transmission electron microscopy and mRFP‐GFP‐LC3 dual fluorescence assays, CCE mitigated autophagic injury, and also down‐regulated autophagy‐related Beclin‐1, LC3II/LC3I ratio, Atg5 and ATF4 levels. Our findings showed the attenuation of CCE on CSE‐induced NHBE cells injury was associated with Nrf‐2‐mediated oxidative signaling pathway.